2017
DOI: 10.1108/jea-03-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Review of conceptual models and methodologies in research on principal instructional leadership in Malaysia

Abstract: Purpose Over the past several decades, instructional leadership has gradually gained increasing currency as a key role of school principals throughout much of the world. This is also the case in Malaysia where educational research, policy and practice have brought the instructional leadership role of the principal front and center. The purpose of this paper is to assess the conceptual models, research methods, and foci of scholars in the study of principal instructional leadership in Malaysia over the past 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 36 publications
6
53
0
1
Order By: Relevance
“…This is especially so in recent times where there is high demand for principals to be accountable to happenings in the school environment and to keep abreast with educational goals. An essential instrument to attain the educational goals by the school principal is through leadership practices, in particular, instructional leadership [11,28,31,37,49].…”
Section: The Principal As Instructional Leadermentioning
confidence: 99%
“…This is especially so in recent times where there is high demand for principals to be accountable to happenings in the school environment and to keep abreast with educational goals. An essential instrument to attain the educational goals by the school principal is through leadership practices, in particular, instructional leadership [11,28,31,37,49].…”
Section: The Principal As Instructional Leadermentioning
confidence: 99%
“…The results showed that cluster school principals engaged a number of teachers in capacity building through inservice training and ongoing professional development. Although training is a particularly important mechanism for improving the quality of teachers (Hallinger, 2005;Hallinger, Adams, Harris, & Suzette, 2018), yet the age limit for teachers to join certified training programs became a major barrier in this case. It is recommended that such age limits must be removed so that school principals are successful in attracting sufficiently qualified candidates and allowing every teacher to maintain and enhance their skills set, including staying up-to-date with the latest developments in pedagogy (Wang, Wang, Li, & Li, 2017;Salleh & Khalid, 2018;Rashdi & Khamis, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the role of SP in schools, besides the focus put by researchers on the so-called instructional leadership (Davis, Darling-Hammond, LaPointe, & Meyerson, 2005;Hallinger, Adams, Harris, & Suzette Jones, 2018;Purinton, 2013), since schools still are also organizations, many conceptual tools of organizational sciences are applicable. Following this line, one of the most relevant topic for Italian SPs is a possible responsibility-authority gap.…”
Section: The Performance Assessment Of Sps: the Contextmentioning
confidence: 99%